2017
DOI: 10.1002/adom.201700373
|View full text |Cite
|
Sign up to set email alerts
|

Van Der Waals Hybrid Perovskite of High Optical Quality by Chemical Vapor Deposition

Abstract: Among different structures, two extreme cases are of special interest: (1) when m goes to infinity, a complete 3D structure is formed due to the absence of larger alkyl amine ligands, e.g., CH 3 NH 3 PbI 3 ; [4] (2) when m goes to 1, smaller alkyl groups are absent and a complete 2D structure is formed where each single layer of lead halide octahedrons is separated by large alkyl groups, i.e., (RNH 3 ) 2 PbX 4 . [5] A finite m value which exceeds unity will lead to multilayers of lead halide octahedrons in eac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
52
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 33 publications
(57 citation statements)
references
References 46 publications
5
52
0
Order By: Relevance
“…Structural phase transitions of (C 4 H 9 NH 3 ) 2 PbI 4 were found to be stopped by substrate interactions . For example, exfoliated (C 4 H 9 NH 3 ) 2 PbI 4 monolayers were transferred to the SiO 2 surface, part of the transferred flakes stayed in the high‐temperature phase until liquid‐helium temperature, whereas without enough substrate interference, the (C 4 H 9 NH 3 ) 2 PbI 4 crystal would undergo a normal phase transition at about 235 K (see Figure i) . In vapor‐synthesized single‐crystalline (C 4 H 9 NH 3 ) 2 PbI 4 flakes, not only was the structural phase transition stopped, but the electron–phonon interaction was also suppressed because of the reduced flake thickness .…”
Section: Exciton Polariton and Electron–phonon Propertiesmentioning
confidence: 99%
“…Structural phase transitions of (C 4 H 9 NH 3 ) 2 PbI 4 were found to be stopped by substrate interactions . For example, exfoliated (C 4 H 9 NH 3 ) 2 PbI 4 monolayers were transferred to the SiO 2 surface, part of the transferred flakes stayed in the high‐temperature phase until liquid‐helium temperature, whereas without enough substrate interference, the (C 4 H 9 NH 3 ) 2 PbI 4 crystal would undergo a normal phase transition at about 235 K (see Figure i) . In vapor‐synthesized single‐crystalline (C 4 H 9 NH 3 ) 2 PbI 4 flakes, not only was the structural phase transition stopped, but the electron–phonon interaction was also suppressed because of the reduced flake thickness .…”
Section: Exciton Polariton and Electron–phonon Propertiesmentioning
confidence: 99%
“…They can be easily grown by both solution methods and vapor transport methods at low temperature, [14][15][16][17] with a tunable bulk direct bandgap. As a consequence of the dielectric and quantum confinement effect, they show strongly bound and stable excitons at room temperature.…”
mentioning
confidence: 99%
“…In 2D Ruddlesden–Popper Perovskite, n values influence directly semiconductor characteristics of provskite films (e.g., exciton binding energy, band gap, and carrier mobility). In the most of studies, researchers assumed to the existence of a certain n ‐value in the films . However, recent papers have showed that the 2D Ruddlesden–Popper perovskite films comprised multiple perovskite phases, even though the films were intended to be prepared as a single‐phase .…”
Section: Crystal Properties In the 2d Ruddlesden–popper Perovskite Filmsmentioning
confidence: 99%
“…In order to achieve a greater PCE based on 2D Ruddlesden–Popper perovskite, Tsai et al . employed a hot‐casting technique to fabricate the 2D layered perovskite thin films (See Figure for the configuration and performance).…”
Section: Lead‐based 2d Ruddlesden–popper Perovskite Solar Cellsmentioning
confidence: 99%
See 1 more Smart Citation